Novas faces da educação superior no Brasil: o neopragmatismo institucionalizado - João dos Silva Reis; Celso Carvalho Prado de Ferraz (EccoS – Revista Científica)
This article purposes to show the neopragmatism like support of higher education reform in Brazil